Influence of micro- and nano-hydroxyapatite coatings on the osteointegration of metallic (Ti6Al4 V) and bioabsorbable interference screws: An in vivo study - Aksakal, B.; Kom, M.; Tosun, H.B.; Demirel, M. (Springer-Verlag France, 2014)
The purpose of this study is to show and compare the fixation and osteointegration capability of metallic and bioabsorbable interference screws. For this, 8 × 20-mm interference screws were implanted into the bone tunnel in the proximal tibial metaphysis of sheep. The nano- (25 nm ± 0.8) and microscale (25 ?m ± 0.5) hydroxyapatite were both dip-coated on Ti6Al4 V interference screws via an in vivo study. After the initial 12 weeks of postoperative, the pullout test, histopathology, X-ray diffraction and scanning electron microscopy examinations were performed. This multidisiplined work showed that the coated screws particularly those with nano-sized-HA coating and the bioabsorbable screws enhanced fixation and provided better stabilization, bone ingrowth and osteointegration than that of uncoated and microscale HA-coated screws. The bioabsorbable screws showed better histopathologic results. © 2013 Springer-Verlag.
Keywords: Coating; Hydroxyapatite; Interference screws; Internal fixation